Talking at Trena's : everyday conversations at an African American tavern - May, Reuben A. Buford, 1965- (New York University Press, 2001)
Talking at Trena's is an ethnography conducted in a bar in an African American, middle-class neighborhood on Chicago's southside. May's work focuses on how the mostly black, working- and middle-class patrons of Trena's talk about race, work, class, women, relationships, the media, and life in general. May recognizes tavern talk as a form of social play and symbolic performace within the tavern, as well as an indication of the social problems African Americans confront on a daily basis. Following a long tradition of research on informal gathering places, May's work reveals, though close description and analysis of ethnographic data, how African Americans come to understand the racial dynamics of American society which impact their jobs, entertainment-particularly television programs-and their social interactions with peers, employers, and others. Talking at Trena's provides a window into the laughs, complaints, experiences, and strategies which Trena's regulars share for managing daily life outside the safety and comfort of the tavern.